Keyhole approaches for surgical treatment of intracranial aneurysms: a short review. (2nd January 2019) - Rychen, Jonathan; Croci, Davide; Roethlisberger, Michel; Nossek, Erez; Potts, Matthew B.; Radovanovic, Ivan; Riina, Howard A.; Mariani, Luigi; Guzman, Raphael; Zumofen, Daniel W.
ABSTRACT: Objective : To clarify the reported experience with keyhole approaches for the treatment of intracranial aneurysms. Methods : The PubMed and Embase databases were searched up to December 2017 for full-text publications that report the treatment of aneurysms with the eyebrow variant of the supraorbital craniotomy (SOC), the minipterional craniotomy, or the eyelid variant of the SOC. The anatomical distribution of aneurysms, the postoperative aneurysm occlusion rate, and the type and rate of complications were examined using univariate analysis. Results : Sixty-seven publications covering treatment of 5770 aneurysms met the eligibility criteria. The reported experience was the largest for the eyebrow variant of the SOC (69.4% of aneurysms), followed by the minipterional approach (28.2%), and the eyelid variant of the SOC (2.4%). The anterior communicating artery (ACoA) was the most frequent aneurysm location for the SOC (eyebrow variant: 33.2%; eyelid variant: 31.2%). The middle cerebral artery (MCA) was the most frequent aneurysm location in the minipterional cohort (55.2%). In the eyelid variant of the SOC cohort, the rate of complete aneurysm occlusion was the lowest (eyelid variant: 90.8%; eyebrow variant: 97.8%, p < 0.001; minipterional approach: 97.9%, p < 0.001), and the postoperative infarction rate was the highest (eyelid variant: 7.2%; eyebrow variant: 3.5%, p = 0.025; minipterional approach: 2.6%, p = 0.003). Conclusion : Each approach has a specific safety and efficacy profile. Surgeons selected the eyebrow variant of the SOC for many aneurysm locations including in particular the ACoA. There is a recent tendency however to opt for the minipterional approach above all for MCA aneurysms. Abbreviations : SOC: Supraorbital Craniotomy; MPT: Minipterional; MCA: Middle Cerebral Artery; ACoA: Anterior Communicating Artery; PCoA: Posterior Communicating Artery; aSAH: Aneurysmal Subarachnoid Hemorrhage; PRISMA: Preferred Reporting Items for Systematic Reviews and Meta-Analyses; MINORS: Methodological Index For Non-Randomized Studies.